Mindful Technical Writing An Introduction to the Fundamentals - Atkinson, Dawn; Corbitt, Stacey (Open textbook library., 2021)
Welcome to Mindful Technical Writing: An Introduction to the Fundamentals, an open textbook designed for use in co-requisite course pairings of developmental writing and introductory technical writing, or indeed in other lower-division college writing courses that focus on building study skills alongside effective workplace and academic writing skills. It offers a no-cost alternative to commercial products, combining practical guidance with interactive exercises and thoughtfully designed writing opportunities. This book’s modular design and ample coverage of topics and genres means that it can be used flexibly over semester-long or stretch courses, allowing instructors and students to select the chapters that are most relevant for their needs. By blending new material with reviews of key topics, such as academic integrity, the chapters provide fresh perspectives on matters vital to the development of strong writing skills.